Inovações ambientais e sistemas nacionais de inovação: caracterizações para o período 1990-2010 - Rosa Livia Goncalves Montenegro (2016)
Environmental damage caused by economic and institutional activities are a recurring concern in debates on the subject. The disposal of industrial wastes vectored by water and air and the emissions of polluting gas go beyond borders. Their external effects triggered thedevelopment of alternative technological solutions. Innovation has a key role so that countries may react against environmental challenges and, at the same time, enhance opportunities for new stimuli. Due to the great relevance and international traits of environmental issues, the objectives for a more sustainable planet become crucial for all countries. They require a wide diffusion of new technologies, support by institutions and new paradigms for production, consumption and disposal of wastes. Current thesis characterizes and identifies possible conditioning factors to the environmental capacity of developed and developing countries.Research initially analyzes the performance of environmental innovations during the 1990s, 2000s and 2010s taking into account the factors that reveal the different degrees of the National Systems of Innovation that trigger the environmental technological development. Patents are employed as proxy for innovation and for the environmental technologicaldevelopment of countries with information retrieved from the European Patent Office (EPO) according to their environmental technological classifications represented by the International Patent Class (IPC). The formulation of four methodological techniques provided a staticmapping of specific configuration and transitivity among groups of forty world economies during analysis and of interaction between scientific areas and technological fields as from environmental patents. Qualitative Comparative Analysis, Clusters Analysis, Discriminating Analysis and Interaction Matrices between Science and Technology were applied. Mainresults contribute towards evolutionary literature and progress (albeit smaller) with regard to the evolution of the National Systems of Innovation of developing countries. International treaties and protocols on the environment have increased the production of environmentaltechnologies during the period under analysis, especially after 1990. Innovations incorporated in the analyses of current thesis identify the specific configurations to innovation of the countries with regard to their environmental conditionings, to the transitivity of countries withdifferent SNIs standards and to asymmetries revealed by Science and Technology for the national scientific bases. These traits contribute towards policy strategies in environmental technological development.